DOCTRINE OF REBUS SIC STANTIBUS AND LAW OF INTERNATIONAL TREATY - Suraputra, D. Sidik (Indonesian Journal of International Law, 2014)
Rebus Sic Stantibus doctrine becomes a dispute as a result from reckless application of States, started from the period towards 1914, to escape from burdensome treaties, and it continued to the period between the First and the Second World War. Rebus Sic Stantibus principle has been applied by many countries and it has been accepted by the majority of international law experts as part of international law. Even though there was a debate about the doctrine application. oktrik The first commentary said by applying negative form would make the fundamental change of circumstances principle. On the other hand, it is not the duty of legislation to define the scope of the fundamental change of circumstances principle, and this duty is granted to law. In the end it depends on the consideration of interested government body in terminating international treaties.